2019
DOI: 10.18632/aging.102032
|View full text |Cite
|
Sign up to set email alerts
|

AGTR1 promotes lymph node metastasis in breast cancer by upregulating CXCR4/SDF-1α and inducing cell migration and invasion

Abstract: The angiotensin II type I receptor (AGTR1) has a strong influence on tumor growth, angiogenesis, inflammation and immunity. However, the role of AGTR1 on lymph node metastasis (LNM) in breast cancer, which correlates with tumor progression and patient survival, has not been examined. AGTR1 was highly expressed in lymph node-positive tumor tissues, which was confirmed by the Oncomine database. Next, inhibition of AGTR1 reduced tumor growth and LNM in orthotopic xenografts by bioluminescence imaging (BLI). Losar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 74 publications
0
45
0
Order By: Relevance
“…In GC, the utility of AGTR1 inhibitor signi cantly suppress GC cell proliferation and stromal brosis [28]. It has been proved that AGTR1 could enhance malignant phenotype of several cancer cells to promote tumor progression [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…In GC, the utility of AGTR1 inhibitor signi cantly suppress GC cell proliferation and stromal brosis [28]. It has been proved that AGTR1 could enhance malignant phenotype of several cancer cells to promote tumor progression [29][30][31].…”
Section: Discussionmentioning
confidence: 99%
“…Yamani et al described that overexpression of AGTR1 was associated with response to rejection after transplantation [43]. Observations by Ma et al showed that AGTR1 can be a useful supplementary marker and explained that overexpression of this gene was strongly associated with promoting epithelial-mesenchymal transition [44], what also showed that during cyclosporine therapy a higher risk of carcinogenesis might be observed [45]. These and our results suggest that during the cyclosporine A treatment, a drug resistance phenomenon may be observed, however its frequency is lower compared with the adalimumab therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was shown that Ang II induced CSC marker expression and facilitated tumor cell survival in NSCLC cells line [77]. Recent data from a breast cancer model revealed an additional mechanism whereby ATR1 promotes tumor cell contraction, migration and invasion by upregulating the C-X-C chemokine receptor type 4 (CXCR4)/Stromal cell derived factor-1α (SDF-1α) signaling through the Focal adhesion kinase (FAK)/Ras homolog family member A (RhoA)/Rho associated kinase 1/2 (ROCK1/2)/Myosin light-chain kinase (MLC) pathway, ultimately inducing metastatic disease [78]. Taken together, these findings support a role for mediators of the Ang II/ATR1 axis as lung cancer modulators, particularly influencing malignant cell growth, dedifferentiation, and migration ( Figure 2).…”
Section: Ace/ang Ii/at1 Receptor Axismentioning
confidence: 99%